Meningkatkan Kemampuan Problem Solving Siswa-Siswi SMA Negeri 7 Semarang melalui Bebras Challenge - Umaroh, Liya; Ningrum, Novita Kurnia; Sukamto, Titien Suhartini (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
Associative and directed thinking are two important ways when a person thinks of an idea that is directly continuous with the emergence of other ideas and in the end has been coherently determined the direction of problem solving. Things like that are often experienced by everyone, especially high school students. The various school assignments they have to do, socialize with school friends, and interact with family at home are so complex that the problems exist that require students to think critically and solve problems well. Bebras Challenge is one of the contests that directs participants, especially high school level, to practice problem solving skills through learning activities by working on problems. The Bebras Challenge activity was attended by various levels of schools, from the lowest levels of Elementary School to Senior High School. SMA Negeri 7 Semarang was one of the participants who took part in the Bebras Challenge, students were encouraged to practice problem solving skills in the contest. The end result of the Bebras Challenge activity is to improve students' abilities in dealing with various problems, one of which is that in the field of subjects in schools, they are able to answer questions in different ways and have the same final result.DOI:Â https://doi.org/10.26905/abdimas.v5i3.4320